On the Asymptotic Behavior of Solutions of the First Initial Boundary-Value Problems for Parabolic Equations - Nguyen Manh Hung; Tran Thi Loan (Український математичний журнал, 2003)
We consider the first initial boundary-value problem for a strongly parabolic system on an infinite cylinder with nonsmooth boundary. We prove some results on the existence, uniqueness, and asymptotic behavior of solutions as t → ∞.